Research on integrated 3D geological modeling of vector grid ——taking the core area of Tianfu New Area as an example - Ming Hao; Peiyao Xie; Huan Liu; Bo Wang; Fang Zhou; Xianglong Zeng; Yang Lei; Deng Pan; Guokun Liao (All Earth)
The development and utilisation of urban underground space is an important part of urban construction, and urban 3D geological modelling is an important standard to evaluate the difficulty of underground space development and utilisation. At present, the urban 3D geological modelling is often the construction of a single expression of the 3D model. Existing urban integration is a fusion and integration of 3D models of different spatial locations, but there is little research on the integration of different expression models in the same spatial location, especially in the integration of 3D geological structure model and 3D geological attribute model. To solve this problem, this paper takes the core business district of Tianfu New District of Chengdu city as the research area and the urban geological survey of Chengdu city as the data base, adopts the borehole-based rapid modelling technology to build the urban 3D geological structure model, uses the grid segmentation and attribute interpolation to realise the model integration, and builds the vector grid integrated 3D geological model of ‘one model, multiple expressions’. It is helpful to comprehensively consider the problems of geological structure and geological properties.